Mental Health Trainings in California's K-12 System Are Associated with Increased Confidence and Likelihood to Intervene with and Refer Students - Osilla, Karen Chan (RAND Corporation, 2015)
Reports on an evaluation of California mental health trainings offered to staff in California's K-12 system.